Local Structure Study of Lanthanide Elements by X‐Ray Absorption Near Edge Structure Spectroscopy. Issue 7 (21st January 2019) - Asakura, Hiroyuki; Hosokawa, Saburo; Teramura, Kentaro; Tanaka, Tsunehiro
Abstract: This paper describes a systematic study of the spectra and local structures of lanthanide (Ln) L‐edge XANES. We found that Ln L1 and L3 ‐edge XANES spectra exhibit characteristic features correlated to their local symmetry through experimental and theoretical simulations. We also propose a simple local structure index criterion for a combination of XANES study and theoretical simulation. Possible solutions of intrinsic problems such as low resolution of characteristic features in the Ln L‐edge XANES and site distributions are also discussed. Abstract : Correlation between pre‐edge peak area of lanthanide L1 ‐edge XANES spectra and bond angle analysis index calculated from bond angle of a lanthanide element and two adjacent oxygen atoms, which can be used for local symmetry analysis of lanthanide elements.